COMPARATIVE STUDY ON PHYSICOCHEMICAL CHARACTERISTICS OF CASSAVA ROOTS FROM THREE LOCAL CULTIVARS IN CÔTE D’IVOIRE - Koko, Casimir Anauma; Kouame, Benjamin Kan; Anvoh, Blanchard Yves; Amani, Georges N’guessan; Assidjo, Emmanuel Nogbou (European Scientific Journal, ESJ, 2014)
This study was aimed to characterize three local cassava cultivars (Akaman, Yace and Zoklo) commonly used and to compare their physicochemical characteristics in order to choose the right roots for the suitable usages. For this purpose, the moisture, ash, starch, protein, lipid, titratable acidity, pH, cyanide, total sugar, carbohydrate, caloric energy, minerals (Ca, Mg, Zn, Fe and P) contents and the Ca/P ratio of roots were evaluated. Data obtained were subjected to chemometric methods (Analysis of variance, Multidimensional Analysis of variance and Cluster analysis). The results showed that roots analyzed had the same general characteristics, whatever the cassava cultivar. Their moisture (60.36-62.18%), energy (385.93-388.63 kcal/100 g), starch (75.36-77.70%) and carbohydrate (92.52- 93.65%) contents were high while the protein (1.95-2.27%), lipid (0.58- 1.04%), ash (2.29-2.67%) and total sugar (2.10-2.64%) contents were low. The significant differences (p<0.05) between the three cassava cultivars were on the physicochemical parameters such as pH, titratable acidity, lipid, cyanide, total sugar and carbohydrate contents. The roots from Yace cultivar are toxic variety and must be processed into various products before consumption. They were characterized by high titratable acidity and carbohydrate, low pH value and total sugar content. The roots from Zoklo cultivar are non-toxic and can be eaten directly, either raw or boiled, or can be processed into various products before consumption. The Akaman roots, characterized by their relatively high lipid content, were intermediate variety and must be processed in order to avoid farther poisoning. Attention must be focused on their utilization form, avoiding consumption as raw.